Usos periodísticos de las Redes Sociales (2018)
Through this research we analyzed effects that has brought the use of social networks, in the development of a responsible journalism, in Santiago de Cali, for the year 2018; Three objectives were raised for this purpose. The first corresponds to the exposure of the new trends of journalism in social networks, starting from the appearance of the WEB 2.0; Secondly, the way some journalists from Santiago de Cali are determined, they use social networks for the development of responsible journalism; Finally it was the journalistic strategies used, to avoid the reproduction of false news that proliferate in the social networks – fake news.